WRITING DIFFICULTIES FACED BY ENGLISH FOREIGN LANGUAGE STUDENTS - Mimin Aminah; Tri Fitri Supriadi (Jurnal Ilmiah Hospitality, 2023)
This abstract provides a summary of the main points related to writing difficulties, writing problems, lack of vocabulary, grammar errors, and a lack of interest in reading. These obstacles significantly impede students' writing skills and overall literacy development. This researcht highlights the interconnections between these challenges and their impact on students' ability to effectively express themselves in writing. It underscores the importance of addressing vocabulary limitations, grammar errors, and promoting reading engagement to improve students' writing proficiency and cultivate a deeper appreciation for language and literacy. By recognizing and tackling these challenges, educators can effectively support students in overcoming writing difficulties and fostering their growth as proficient writers